Public policy, political connections, and effective tax rates: Longitudinal evidence from Malaysia - Adhikari, Ajay; Derashid, Chek; Zhang, Hao (Elsevier Inc, 2006)
This study examines the link between effective tax rates (ETR) and political connections in developing economies. The political connections explanation is informed by the observation that developing economies tend to be “relationship-based” rather than “market-based” capitalisms. Two proxies of political patronage are developed and applied to a group of Malaysian firms over a 10-year period. We find firms with political connections pay tax at significantly lower effective rates than other firms. Our results suggest that political connections are an important determinant of ETR in relationship-based economies.